2023
DOI: 10.1021/acsami.3c00269
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Low-Frequency Response of Impedance Spectroscopy of Halide Perovskite Single Crystals Using Machine Learning

Abstract: Electrochemical impedance spectroscopy (EIS) has emerged as a versatile technique for characterization and analysis of metal halide perovskite solar cells (PSCs). The crucial information about ion migration and carrier accumulation in PSCs can be extracted from the low-frequency regime of the EIS spectrum. However, lengthy measurement time at low frequencies along with material degradation due to prolonged exposure to light and bias motivates the use of machine learning (ML) in predicting the low-frequency res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The EIS Nyquist spectra, acquired under bias voltages ranging from 0.1 to 1.5 V, reflect the evolving electrical behavior of the MAPbI 3 SC, as indicated by the correspondingly decreasing radii of the semicircular Nyquist graphs in Figure . This trend of decreasing Z ′ and Z ″ continues in each corresponding increasing bias voltage . As we increased the bias voltage across the MAPbI 3 SC, the EC type of the EIS spectra transformed.…”
Section: Resultsmentioning
confidence: 75%
“…The EIS Nyquist spectra, acquired under bias voltages ranging from 0.1 to 1.5 V, reflect the evolving electrical behavior of the MAPbI 3 SC, as indicated by the correspondingly decreasing radii of the semicircular Nyquist graphs in Figure . This trend of decreasing Z ′ and Z ″ continues in each corresponding increasing bias voltage . As we increased the bias voltage across the MAPbI 3 SC, the EC type of the EIS spectra transformed.…”
Section: Resultsmentioning
confidence: 75%
“…In addition to this, the effect and underlying mechanism of hysteresis in relation to device performance can be understood with the help of impedance spectroscopy (IS). , The presence of hysteresis or accumulation of ions will lead to a significantly higher value of capacitance at low frequency. Tisdale et al studied the effect of different contact materials on MAPbBr 3 crystals and found that the gold (Au) contact leads to high resistive and capacitive effects at lower frequencies in electrochemical impedance spectroscopy (EIS) spectra.…”
Section: Introductionmentioning
confidence: 99%
“…As an important semiconductor functional material, lead halide perovskite plays an important role in the light, display, and photodetector fields due to its excellent optoelectronic properties [1][2][3][4][5][6]. Although lead halide perovskites have achieved a series of remarkable results [7,8], their inherent toxicity and poor stability limit their further applications in optoelectronic devices. Therefore, the key to solving these problems is to explore new non-toxic and stable materials.…”
Section: Introductionmentioning
confidence: 99%